Inhibition of KCa2 and Kv11.1 Channels in Pigs With Left Ventricular Dysfunction - Citerni, Carlotta; Kirchhoff, Jeppe; Olsen, Lisbeth Høier; Sattler, Stefan Michael; Grunnet, Morten; Edvardsson, Nils; Bentzen, Bo Hjorth; Diness, Jonas Goldin (Frontiers in Pharmacology, 2020)
Background Inhibition of KCa2 channels, conducting IKCa, can convert atrial fibrillation (AF) to sinus rhythm and protect against its induction. IKCa inhibition has been shown to possess functional atrial selectivity with minor effects on ventricles. Under pathophysiological conditions with ventricular remodeling, however, inhibiting IKCa can exhibit both proarrhythmic and antiarrhythmic ventricular effects. The aim of this study was to evaluate the effects of the IKCa inhibitor AP14145, when given before or after the IKr blocker dofetilide, on cardiac function and ventricular proarrhythmia markers in pigs with or without left ventricular dysfunction (LVD). Methods Landrace pigs were randomized into an AF group (n = 6) and two control groups: SHAM1 (n = 8) and SHAM2 (n = 4). AF pigs were atrially tachypaced (A-TP) for 43 ± 4 days until sustained AF and LVD developed. A-TP and SHAM1 pigs received 20 mg/kg AP14145 followed by 100 µg/kg dofetilide whereas SHAM2 pigs received the same drugs in the opposite order. Proarrhythmic markers such as short-term variability of QT (STVQT) and RR (STVRR) intervals, and the number of premature ventricular complexes (PVCs) were measured at baseline and after administration of drugs. The influence on cardiac function was assessed by measuring cardiac output, stroke volume, and relevant echocardiographic parameters. Results IKCa inhibition by AP14145 did not increase STVQT or STVRR in any of the pigs. IKr inhibition by dofetilide markedly increased STVQT in the A-TP pigs, but not in SHAM operated pigs. Upon infusion of AP14145 the number of PVCs decreased or remained unchanged both when AP14145 was infused after baseline and after dofetilide. Conversely, the number of PVCs increased or remained unchanged upon dofetilide infusion. Neither AP14145 nor dofetilide affected relevant echocardiographic parameters, cardiac output, or stroke volume in any of the groups. Conclusion IKCa inhibition with AP14145 was not proarrhythmic in healthy pigs, or in the presence of LVD resulting from A-TP. In pigs already challenged with 100 µg/kg dofetilide there were no signs of proarrhythmia when 20 mg/kg AP14145 were infused. KCa2 channel inhibition did not affect cardiac function, implying that KCa2 inhibitors can be administered safely also in the presence of LV dysfunction.